Musculoskeletal pain and loneliness, social support and social engagement among older adults: analysis of the Oxford Pain, Activity and Lifestyle Cohort - Nicolson, P; Williamson, E; Morris, A; Sanchez, M; Bruce, J; Silman, A; Lamb, S (Wiley, 2020)
Background Musculoskeletal (MSK) pain is common in older adults. Physical and psychological consequences of MSK pain have been established, but it is also important to consider the social impact. We aimed to estimate the association between MSK pain and loneliness, social support and social engagement.